Phyllagathis guidongensis (Melastomataceae), a new species from Hunan, China - Tian, Jing; Pen, Ling; Zhou, Jian-Cheng; Tian, Xue-Hui; Yi, Ren-Yuan; Liu, Lei; Cai, Xiu-Zhen; Kuang, Ren-Ping; Liu, Ke-Ming (Phytotaxa, 2016)
Phyllagathis guidongensis K. M. Liu & J. Tian, a new species of Melastomataceae from Hunan Province, China, is described and illustrated. The new species is similar to Phyllagathis stenophylla, but it is obviously different from the latter by its creeping stolons 10–30 cm long, prostrate lower part of the stems narrowly elliptic leaf blade, 1.8–3.0 × 0.5–1.0 cm, apex obtuse or shortly acuminate, both sides sparsely covered with bristles and villose, adaxial surface densely covered with yellow glandular dots solitary flowers, and capsules not obviously angulate.